Multi-habitat seascape restoration: optimising marine restoration for coastal repair and social benefit - McAfee, Dominic; Reis-Santos, Patrick; Jones, Alice R.; Gillanders, Bronwyn M.; Mellin, Camille; Nagelkerken, Ivan; Nursey-Bray, Melissa J.; Baring, Ryan; da Silva, Graziela Miot; Tanner, Jason E.; Connell, Sean D. (Frontiers in Marine Science, 2022)
Marine ecosystem restoration is fast becoming the primary tool for repairing the socio-ecological functions and economic benefits of coastal ecosystems. Healthy seascapes are characterized by many interacting species and intermingled habitats (e.g., seagrass, kelp, shellfish, sedimentary) that co-create ecological functions of substantial socio-economic value. These co-created functions not only build stability and resilience at seascape scales, but synergistically combine to enhance ecological productivity that is greater than the sum of the individual habitats. Yet, restoration practice is dominated by single-habitat approaches underpinned by single-species monocultures, potentially limiting the range of benefits that restoration can provide. We propose that for ecosystem restoration to meet its full potential in delivering socio-ecological benefits that are resilient to environmental change, restoration practices should plan beyond single-species and single-habitats to a multi-habitat seascape. Where multiple habitats are co-restored, their positive interactions mutually benefit each other to stabilize and even accelerate ecosystem recovery; such as co-restored shellfish and kelp forests on constructed reefs, which combine to stabilize sediment for seagrass recovery. As fisheries scientists and managers, food and social scientists, and ecologists and oceanographers, we describe multi-habitat marine restoration activities that are readily achievable and provide a vision for the diverse socio-ecological, economic, and culture benefits that may emerge from future seascape-level repair.